Evaluation of Conventional and New Maximum Heart Rate Prediction Models for Individuals - Aragón Vargas, Luis Fernando (2014)
In October of 1992 I submitted an abstract to the American College of Sports Medicine, co-authored with Dr. Schork and Dr. Edington from the University of Michigan, to present our study at the 1993 Annual Meeting. A few weeks later I received Volume 24, issue 10 of Medicine and Science in Sports and Exercise, where Whaley and colleagues had published a similar paper. Discouraged by the bad timing, I never tried to publish my own paper. Several years later, other similar papers have been published, arguing for a correction to the conventional 220-age formula for maximum heart rate. I realized I should have tried to publish my paper back in 1993! I have dug out the original poster presentation materials, scanned them, and prepared this document for the sake of teaching my students (who often quote Tanaka et al. and Gellish et al.) the importance of prompt publication of their work.